Students' perceptions on the integration of sexual and gender minority constructs within the dental curriculum - Ellevera, Janine Thea D.; Salvacion, Maria Lourdes Dorothy S. (Manila National Teacher Training Center for the Health Professions, University of the Philippines Manila, 2022)
As the sexual and gender minorities (SGMs) are at risk for various health disparities, the World Health Organization (WHO) calls for the training of healthcare providers to demonstrate cultural competence when dealing with members of the population to address their specific needs. To facilitate this, various studies have suggested the inclusion of SGM-specific constructs in the required curriculum and to complement it with campus climate-related efforts. This is a descriptive study that explored the student’s perceptions on the integration of SGM-specific constructs into the curriculum and the campus climate of a dental school in the Philippines. A convergent parallel mixed-methods design was employed, given the complexity of the phenomenon under study. A two-stage stratified random sampling method was employed for the quantitative part and the sample size was computed using Cochran's Formula. A purposive sampling method was employed for the qualitative part by recruiting the student council's year-level officers. The quantitative part studied the extent to which the SGM-specific constructs are covered in the required curriculum. A two-part survey questionnaire was developed and administered to the dental students. Semi-structured interviews were conducted to discuss the existing campus climate towards the SGM population. Survey results show that coverage varies for each concept. The most-reported covered concepts are oral manifestations of sexually transmitted diseases and use of inclusive terminologies. The strategy most employed for coverage is through didactic lectures. The student leaders described the campus climate towards the SGM population as neutral. However, their interview responses reveal heteronormativity in the organizational and behavioral dimensions of the campus climate. The integration of the quantitative and qualitative data reveals incongruences between the perceived coverage in the required curriculum and the perceived campus climate. This suggests that SGM-specific constructs are not well-integrated within the dental curriculum. It also implies the need for additional research exploring the correlation of the integration of SGM-specific constructs and climate-related efforts in developing cultural competence towards the population. These findings are expected to add to the body of knowledge on the dental curriculum in the Philippines.
Thesis
Keywords: Education, Dental; Sexual and gender minorities